International Logistics: Mission and Functions - Sherkulovna, Bababekova Dilfuza; Baxriddinovna, Aminova Niginabonu; Rasul-kizi, Kadirova Dilnoza (European Journal of Life Safety and Stability (2660-9630), 2022)
Today, logistics is one of the growing industries. In particular, international transportation and reduction of costs, tracking of cargo on the road are modern requirements. That is why this article analyzes the importance of international logistics, its tasks, functions and ways of development. Modern international logistics of space and borders is considered by experts as a concept of managing the flow of goods, cargo (material), intangible and passenger between countries and continents in time, space and socio-economic environment.